Influential Factors of the Static Shear Properties of Coral Mud in the South China Sea - Yang Shen; Xiaoxi Rui; Long Yang; Shaoyu Li; Xue Shen (Advances in Civil Engineering)
Coral mud, a kind of special material used for constructing islets in reclamation projects, is widely spread in the South China Sea. Combined with microstructure research, a series of triaxial tests were performed in this paper to study the static shear strength characteristics and potential factors that can influence them. The effective stress path was similar to the total stress path because of the unique microstructure resulting in a high strength and a high dissipation rate of the pore pressure in the coral mud. The initial void ratio and the initial confining pressure affected the strength and deformation characteristics of the coral mud. When the soil came to failure, the pore pressure coefficient Af varied linearly with the initial void ratio. The critical friction angle was greatly influenced by the confining pressure, and its magnitude first developed to a peak value and then decreased as the void ratio increased. This change showed that there was a linear relationship between the initial elastic modulus E0i and lgp0 as well as between the secant modulus E50 and p0. The estimation ability of Cam-Clay was verified in this research. The value of parameter λ was determined incrementally by a larger initial void ratio, while the value of parameter M decreased smoothly first and then rose slightly; the selection of parameter κ was approximately 0.0035. The results supported that the Cam-Clay model is able to simulate the stress-strain relationship of coral mud, and a referenced estimation can be reliably and efficiently obtained for the reclamation projects of constructing islets.